Uwagi o zrozumiałości dziennikarskich tekstów prawniczych - Araczewska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article represents an attempt at identifying linguistic phenomena typically present in journalists’ texts concerning problems of law and aimed at non-professionals. Its objective is to evaluate the influence of these phenomena on the general comprehensibility of this kind of text. For a text to be called communicative, it has to enable each of its recipients to fully comprehend it (general comprehension) in a way that is appropriate to the author’s intentions (adequate comprehension), and does not require great effort from the reader (easiness of comprehension). In practice, factors determining a moderate grade of communicativeness are: use of complicated syntactic constructions, direct adoption of the content of legal regulations, and employment of stylistics characteristic of official texts. The consequence of shaking the balance between a publicistic and official style creates stylistic dissonance, which negatively affects the ease of comprehension.